2016
DOI: 10.1007/s10695-016-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of pulp and paper mill effluent on two commonly cultured carps: a SEM- and EDS-based hematological biomarker analysis

Abstract: Blood being a vehicle for the transport of industrial pollutants in living system, fish hematology is considered as potent biomarker. In the present study, we investigated respective sublethal effects of pulp and paper mill effluents on hematology of two commonly cultured carps, Cyprinus carpio and Ctenopharyngodon idella, using optical, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Irrespective of species, results showed significant decrease in erythrocyte, hematocrit and hemoglobin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…SEM studies of erythrocytes revealed various abnormalities such as irregular shape, notched, elongated cells, cytoplasmic bleb in C. punctatus . Various researchers observed different abnormalities in erythrocytes of fish exposed to different xenobiotics ( Dey et al, 2016 , Kaur and Kaur, 2015 , Mehra and Chadha, 2021 ). Changes in the morphology of erythrocytes of fish exposed to xenobiotics indicate the poor health status of the fish ( Sawhney and Johal, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…SEM studies of erythrocytes revealed various abnormalities such as irregular shape, notched, elongated cells, cytoplasmic bleb in C. punctatus . Various researchers observed different abnormalities in erythrocytes of fish exposed to different xenobiotics ( Dey et al, 2016 , Kaur and Kaur, 2015 , Mehra and Chadha, 2021 ). Changes in the morphology of erythrocytes of fish exposed to xenobiotics indicate the poor health status of the fish ( Sawhney and Johal, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elliptocyte (EL, El): [30,47,49,87,93,126,129,130,140,152]. Dacrocyte (Da, Tr): [4,47,77,87,96,129,140,152,153]. Schistocyte (Sch, Sh): [5,69,77,130,154,155].…”
Section: Acanthocytementioning
confidence: 99%
“…Acanthocytosis has been associated with liver dysfunction [29], suggesting a possible link between drug administration, organ damage, and poikilocytosis. In fish, acanthocytes have been observed during hemolytic, microcytic, and normocytic anemia induced by heavy metal intoxication, paper mill effluents, pharmaceutical application, pesticide application, and many more [50,75,96,100], but their pathological significance has not been studied yet. Acanthocytes have been observed in every reported case of poikilocytosis in fish (Table 2).…”
Section: Acanthocytementioning
confidence: 99%